(untitled) (Philology, 2019)
The issue of security plays a central role in the election campaigns of the right-wing populist “Alternative für Deutschland” (AfD). This is shown in the present article on the basis of election posters from 2016 to 2018. First of all, a statistical analysis of the word material found on the posters was carried out. This analysis clearly shows that security-related lexis occurs frequently in the corpus examined. Selected examples are used to illustrate how the security topic is implemented multimodally on the election posters. This shows that the AfD prefers to associate crime with immigration. Immigration thus poses a threat to security, so that from the point of view of the AfD the prevention or reduction of immigration is necessary in order to combat crime.